Clinical features of patients with IgG4-related disease complicated with perivascular lesions. Issue 1 (January 2015) - Ebe, Hiroshi; Tsuboi, Hiroto; Hagiya, Chihiro; Takahashi, Hiroyuki; Yokosawa, Masahiro; Hagiwara, Shinya; Hirota, Tomoya; Kurashima, Yuko; Takai, Chinatsu; Miki, Haruka; Asashima, Hiromitsu; Umeda, Naoto; et al.
Abstract Objective. To define the clinical features of IgG4-related disease (IgG4-RD) complicated with perivascular lesions. Methods. The clinical features of seven patients with IgG4-RD and perivascular lesions diagnosed at the University of Tsukuba Hospital between October 2008 and October 2013, were analyzed, including clinical background, results of imaging studies, satisfaction of the 2011 comprehensive diagnostic criteria (CDC) for IgG4-RD, laboratory data, distribution of perivascular lesions, involvement of other organs, and response to steroid therapy. Results. We studied six men and one woman with a mean age of 66.9 ± 6.7 years (± SD). Six of seven patients were diagnosed as definite IgG4-RD, while the seventh was considered possible IgG4-RD, based on the CDC for IgG4-RD. Serum IgG4 levels at diagnosis were higher than 135 mg/dl in all seven patients (mean, 933 ± 527). Serum C-reactive protein (CRP) levels were elevated in two only (mean, 1.42 ± 3.56 mg/dl). The perivascular lesions were located in the pulmonary artery (n = 1), thoracic aorta (n = 2), abdominal aorta (n = 6), coronary (n = 1), celiac (n = 1), superior mesenteric (n = 1), renal (n = 2), inferior mesenteric (n = 5), and iliac (n = 3) arteries. In addition to perivascular lesions, six patients showed involvement of other organs. All seven patients were treated with prednisolone (0.6 mg/kg/day), which rapidly improved the perivascular and other organ lesions in six patients (the other one patient have not yet been evaluated due to the short follow-up). Conclusion. Perivascular lesions show wide distribution in patients with IgG4-RD. Serum CRP levels are not necessarily elevated in these patients. Steroid therapy is effective in IgG4-RD and results in resolution of lesions.